SWOT Analysis and Developing Strategies for the Realisation of Urban Livability in Tehran. Issue 1 (2nd January 2021) - Shabanzadeh Namini, Reza; Loda, Mirella; Meshkini, Abolfazl
ABSTRACT: The present study aims to analyse the strengths, weaknesses, opportunities and threats (SWOT) of managing the Tehran Metropolitan to help comprehend the status quo as well as the challenges to the realisation of liveability indicators. The data were collected from numerous sources including literature review, library resources, public reports, interviews with urban executives and urban management experts, and questionnaires. The study opens a new window through which the main stakeholders and urban managers can understand the internal and external conditions of urban management as well as the challenges to liveability in the city. Seven critical strategies based on SWOT identification are presented with an emphasis on research results. Such strategies can promote the realisation of liveability and inform the future development of the city on a strategic level.